2013
DOI: 10.1080/02786826.2013.803018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Measured Particle Lung-Deposited Surface Area Concentrations by an Aerotrak 9000 Using Size Distribution Measurements for a Range of Combustion Aerosols

Abstract: Surface area in addition to mass concentration is increasingly being emphasized as an important metric representing potential adverse health effects from exposure to inhaled particles. Lungdeposited surface area (SA) concentrations for a variety of aerosols: coal, biomass, cigarette, incense, candle, and TiO 2 were measured using an AeroTrak 9000 (TSI Incorporated) and compared with those calculated from number size distributions from a scanning mobility particle sizer (SMPS). Three methodologies to compute th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…An EL‐USB‐CO EasyLog (LASCAR Electronics, Erie, PA 16505) was used to monitor CO concentrations. More details about the operating principles of the three instruments can be found in previous studies (Leavey, Fang, Sahu, & Biswas, ; Leavey et al, ; Patel, Leavey, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…An EL‐USB‐CO EasyLog (LASCAR Electronics, Erie, PA 16505) was used to monitor CO concentrations. More details about the operating principles of the three instruments can be found in previous studies (Leavey, Fang, Sahu, & Biswas, ; Leavey et al, ; Patel, Leavey, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Lung-deposited surface area (SA) was measured using an AeroTrak 9000 Nanoparticle Aerosol Monitor (TSI Inc.), reporting the fraction of SA of particles in the size range 0.01 to 1 μm 2 /cm 3 that would deposit in different regions of the respiratory tract according to the IARC. A more complete description is provided in Leavey et al, (2013). For this study, the fraction of particles depositing in the alveolar (A) region was collected.…”
Section: Methodsmentioning
confidence: 99%
“…Otherwise, the NSAM compared well, within about 720%, with the predicted value from the SMPS measurements. Leavey, Fang, Sahu, and Biswas (2013) investigated the performance of Aerotrak 9000 for a variety of aerosols: coal, biomass, cigarette, incense, candle and TiO 2 . They found that with the exception of coal combustion particles, overestimated by Aerotrak by almost 35% for the TB region, and 28% for the alveolar region, the Aerotrak consistently underestimated the reference SMPS values.…”
Section: Introductionmentioning
confidence: 99%